Surface chemistry of black phosphorus under a controlled oxidative environment. (23rd September 2016) - Luo, Wei; Zemlyanov, Dmitry Y; Milligan, Cory A; Du, Yuchen; Yang, Lingming; Wu, Yanqing; Ye, Peide D
Abstract: Black phosphorus (BP), the bulk counterpart of monolayer phosphorene, is a relatively stable phosphorus allotrope at room temperature. However, monolayer phosphorene and ultra-thin BP layers degrade in ambient atmosphere. In this paper, we report the investigation of BP oxidation and discuss the reaction mechanism based on the x-ray photoelectron spectroscopy (XPS) data. The kinetics of BP oxidation was examined under various well-controlled conditions, namely in 5% O2 /Ar, 2.3% H2 O/Ar, and 5% O2 and 2.3% H2 O/Ar. At room temperature, the BP surface is demonstrated not to be oxidized at a high oxidation rate in 5% O2 /Ar nor in 2.3% H2 O/Ar, according to XPS, with the thickness of the oxidized phosphorus layer <5 Å for 5 h. On the other hand, in the O2 /H2 O mixture, a 30 Å thickness oxide layer was detected already after 2 h of the treatment. This result points to a synergetic effect of water and oxygen in the BP oxidation. The oxidation effect was also studied in applications to the electrical measurements of BP field-effect transistors (FETs) with or without passivation. The electrical performance of BP FETs with atomic layer deposition (ALD) dielectric passivation or h-BN passivation formed in a glove-box environment are also presented.